For whiterum! O neomedievalismo na capital de Skyrim - Santos, Beatriz Faria [UNIFESP] (2020)
The Elder Scrolls are a series of eletronic games produced by Bethesda between 1994 and 2017. In it’s fifth and more recente volume, named The Elder Scrolls V: Skyrim, launched in 2011, it can be observed in the digital world a city called Whiterum, whose narrative and visual conception aimed to re-translate medieval images in a dinamic of usage and appropriation that call back to the medievalism and neomedievalism conceptions frequently used amongst visual production in the last centuries. It is clear that several parts of the city – as well as the characters that live there – relate themselves to the neomedievalist conception of High Medieval scandinavian art and culture, in what can be perceived as a readaptation of an idea of a idealized “North”. In this sense, considering the new discussions around artistic mobility on Art History and Cultural History, we will discuss the relation between the city of Whiterum, its characters and the neomedievalist recreations about an idealized Middle Ages.